2011
DOI: 10.1097/jom.0b013e318204fa7f
|View full text |Cite
|
Sign up to set email alerts
|

An Observed Relationship Between Vestibular Function and Auditory Thresholds in Aircraft-Maintenance Workers

Abstract: This study has demonstrated a relationship between low-frequency hearing loss, vestibular dysfunction, anxiety, and depression in an occupational population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…From a more theoretical standpoint, the current findings also support the mounting evidence of vestibular damage and balance disorder potentiated by NIHL (Juntunen et al, 1987; Guest et al, 2011; Kumar et al, 2010; Sazgar et al, 2006; Golz et al, 2001; Shupak et al, 1994; Manabe et al, 1995; Pyykkö et al, 1989; Oosterveld et al, 1982; McElhinney et al, 1998; Van der Laan 2001; Termoz & Prince, 2005; Gerson, Jarjoura, & McCord, 1989). This is not to minimize the potential contribution of hearing loss in treating information that may hinder mobility (Viljanen et al, 2009a, 2009b).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From a more theoretical standpoint, the current findings also support the mounting evidence of vestibular damage and balance disorder potentiated by NIHL (Juntunen et al, 1987; Guest et al, 2011; Kumar et al, 2010; Sazgar et al, 2006; Golz et al, 2001; Shupak et al, 1994; Manabe et al, 1995; Pyykkö et al, 1989; Oosterveld et al, 1982; McElhinney et al, 1998; Van der Laan 2001; Termoz & Prince, 2005; Gerson, Jarjoura, & McCord, 1989). This is not to minimize the potential contribution of hearing loss in treating information that may hinder mobility (Viljanen et al, 2009a, 2009b).…”
Section: Discussionsupporting
confidence: 86%
“…Sensory deficits (visual and auditory) are recognized as risk factors for falls among older adults (Keller, Morton, Thomas, & Potter, 1999; Kulmala et al, 2009; Viljanen et al, 2009a). Permanent vestibular dysfunction interfering with the maintenance of balance (control and body sway; Juntunen et al, 1987) would be the most likely causative factor (Golz et al, 2001; Guest, Boggess, D’Este, Attia, & Brown, 2011; Kumar, Vivarthini, & Bhat, 2010; Manabe, Kurokawa, Saito, & Saito, 1995; Oosterveld, Polman, & Schoonheyt, 1982; Pyykkö, Aalto, & Ylikoski, 1989; Sazgar, Dortaj, Akrami, Akrami, & Karimi Yazdi, 2006; Shupak et al, 1994). According to Sazgar et al (2006), damage to the vestibular system, especially to the saccule, is a potential problem with cochlear-damaging factors because saccule receptors are coupled physically with the auditory receptors; that is, they share the membranous labyrinth.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Thakur et al (2004) found that the continuous exposure to the relatively high level of noise in the surroundings of an airport is likely to affect the central pathway of the auditory system. This was also confirmed by others (Chen et al, 1992; Guest et al, 2011) where a damage of both peripheral cochlear organs and the central auditory pathway by high-frequency aircraft noise exposure was reported. According to the Egyptian Environmental Law (1994), working hours should be reduced to half for every 5 dB above the permissible limit which is 90 dB.…”
Section: Discussionsupporting
confidence: 85%
“…Agrawal and colleagues (Agrawal et al 2009(Agrawal et al , 2013 reported that 35% of adults older than 40 yr had evidence of postural instability and that balance dysfunction increased with age so that by 80 yr, 85% of adults reported balance problems. Although the causes of balance dysfunction are complex and multifactorial, multiple studies suggest there may be a linkage between hearing loss and vestibular dysfunction in humans (Akin et al 2012;Guest et al 2011;Heitz et al 2019;Lin and Ferrucci 2012;Manabe et al 1995;Oosterveld et al 1982;Shupak et al 1994;Yilmaz et al 2018;Ylikoski and Ylikoski 1994;Ylikoski et al 1988;Zuniga et al 2012). Noise exposure as a risk factor for vestibular loss has obvious public health implications, but there is a lack of evidence for a causal connection between noise exposure and vestibular loss.…”
Section: Introductionmentioning
confidence: 99%